Intellectual Property Strategy Transformation for Digital Retrofitting of Industrial Products - Andersson, Sebastian; Elm, Gustav (My University, 2026)
This thesis investigates how an industrial company’s intellectual property (IP) strategy transforms when a legacy physical product is digitally retrofitted and connected to digital ecosystems. Grounded in Industry 4.0, the Internet of Things (IoT), and servitization, the thesis provides an empirically grounded transformation map (gap analysis) of how value creation and appropriation shift from a pre-digital, artifactcentered era, where patents and design rights were primary, to a post-retrofitting context in which control over data, software, algorithms, interfaces, and relationships becomes increasingly essential. The thesis is based on an abductive exploratory case study in a European context. The empirical material consists of 29 semi-structured interviews with employees at the case company, across R&D, Strategy, Sales, and Law/IP. The findings show that real-time access to product-generated data, together with insights derived from it, becomes a central asset. These capabilities enable new services such as predictive maintenance and support emerging business models based on subscriptions, leasing, and outcome-based agreements. At the same time, retrofitting introduces additional risks, particularly related to cybersecurity, brand reputation, and difficulty detecting digital IP intrusions. Traditional IP remains important as a foundational layer, signaling reliability and regulatory compliance. Meanwhile, new digital assets are increasingly complemented by trade secrecy, contractual agreements, and control over APIs, standards, and data access to manage new ecosystem dependencies and reduce the risk of disintermediation. The thesis also finds implications for a hybrid, layered IP strategy for digital retrofitting, in which formal IPRs and IP mechanisms jointly support appropriability across the physical and digital layers. Furthermore, it highlights the tension between regulatory demands for data sharing, such as those introduced by the Data Act, and the strategic need to maintain exclusivity. This tension underscores the importance of carefully designed contractual agreements, classification of trade secrets, and technical access controls to ensure appropriability and long-term competitiveness as new and established actors compete for control of the customer interface. The main changes between the pre- and post-digitalization eras of IP strategy are synthesized and summarized in an overview table, providing a structured representation of the thesis’ key findings.
Keywords: Intellectual Property Strategy; Appropriability Regimes; Servitization; Internet of Things (IoT); Digital Ecosystems; Digital Retrofitting